2019
DOI: 10.5897/jmpr2019.6772
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of selected Ethiopian medicinal plants used in traditional breast cancer treatment against breast-derived cell lines

Abstract: Traditional medicine is widely practiced in Ethiopia. Here we investigate the toxicity of extracts of seven medicinal plants traditionally used to treat breast cancer in Ethiopia. These plants, Sideroxylon oxyacanthum, Zanthoxylum chalybeum, Clematis simensis, Clematis longicauda, Dovyalis abyssinica, Vernonia leopoldi, and Clerodendrum myricoides, were selected based on recommendations by traditional healers and on the frequency of use. After harvesting the plant material, the water content was determined and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The questionnaire was divided into two sections (A and B). In section A, socio-demographic information of the respondents was recorded, while information on the plants used for the management of cancer was recorded in section B. Twenty (20) respondents were selected from each LGA. Before the interviews, consent approvals were secured from local authorities.…”
Section: Data Collectionmentioning
confidence: 99%
“…The questionnaire was divided into two sections (A and B). In section A, socio-demographic information of the respondents was recorded, while information on the plants used for the management of cancer was recorded in section B. Twenty (20) respondents were selected from each LGA. Before the interviews, consent approvals were secured from local authorities.…”
Section: Data Collectionmentioning
confidence: 99%
“…Recently, Birhan and coworkers reported that an 80% methanol extract displayed that Staphylococcus aureus was the most susceptible bacteria, followed by Pseudomonas aeruginosae [8]. The chloroform fraction of Clematis simensis was cytotoxic against breast cancer cell lines (JIMT-1, MCF-7, and HCC1937) [14].…”
Section: Introductionmentioning
confidence: 99%